Impact of COVID-19: Dietary Consumption Patterns and Family Nutritional Intake - Inna Sholicha; Aida Ratna Wijayanti (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
The COVID-19 pandemic has caused various very drastic changes related to the nutritional and economic needs of families in Indonesia. The existence of differences in instant food consumption dominates to cause nutritional intake of nutrients that do not meet the body’s needs. This research aims to identify patterns of food consumption and family nutritional intake. This research method uses a quantitative type and the design is survey analytics. The population was 500 people, because of the pandemic red zone area, a limited study sample of 30 respondents was taken with purposive sampling on the head of the family in Ronowijayan Siman Ponorogo. Food consumption patterns and nutritional intake were determined based on interviews with respondents using a 24-hour Recall questionnaire. The research data were analysed using Kendall-Tau with a value of alpha more than a sig value of 0.05 more than 0.010 so that it was stated to have a significant relationship with the value of the coefficient of very weak correlation of consumption patterns with family nutritional intake. Good consumption patterns and nutritional intake can strengthen immunity, indirectly reducing COVID-19 infection transmission for families.